Myeloid/lymphoid neoplasm with CEP110-FGFR1 fusion: An analysis of 16 cases show common features and poor prognosis. Issue 1 (1st January 2021) - Chen, Meiyu; Wang, Kai; Cai, Xiaohui; Zhang, Xiuwen; Chao, Hongying; Chen, Suning; Shen, Hongjie; Wang, Qian; Zhang, Ri
ABSTRACT: Objectives: The 8p11 myeloproliferative syndrome (EMS) is an extremely rare, generally aggressive haematologic malignancies. This study provided the clinical outcomes and therapeutic strategies for EMS patients confirmed with CEP110-FGFR1 fusion. Methods: We report here a case of translocation (8;9) (p12;q33)/CEP110-FGFR1 who received allo-HSCT and achieved molecular remission. We searched the PubMed database for relevant medical literatures published between 1992 and 2018. We generalized the laboratory results, clinical features, therapeutic outcomes for EMS with confirmed CEP110-FGFR1 fusion. Results: We identified 16 EMS cases with CEP110-FGFR1 fusions including our patient. The observed common syndrome features were characterized as follows: a male predominance, fatigue (35.7%), tonsil hypertrophy (41.7%), lymphadenopathy (53.8%), hepatosplenomegaly (54.5%). leukocytosis (greater than 20.0 × 10 9 /L, 71.4%), coexisting of eosinophilia and monocytosis (93.3%), and frequent progression to acute leukaemia. High incidence of tonsil hypertrophy and monocytosis may be a feature of EMS with CEP110/FGFR1 fusions. The CR rate for EMS was 23.1%. One patient treated with highly selective FGFR kinase inhibitor, INCB054828, achieved complete molecular remission rapidly. Allo-HSCT was performed in 8 patients. The median survival time for those patients was 9.0 (95%CI 5.599–12.601) months, with a range between 5 and 27 months. Allogeneic HSCT could improve survival in selected patients. Conclusion: FGFR1 and RUNX1 may be potential therapeutic targets for clinical trials. More accumulation of cases is also needed to determine whether allo-HSCT could be an optimal approach.